Instilling Morals: Affective Value Formation Strategies in Islamic Education - Alan Wahyu Pratama; Mohammad Zakki Azani; Gheida Abdala (JIE (Journal of Islamic Education), 2025)
This study aims to analyze the strategies of Islamic Education teachers in instilling morals in students in order to form affective values. This study aims to identify the strategies implemented by Islamic Education teachers in instilling morals in students to develop affective values. The main focus of this study is to understand the extent to which the implemented strategies are able to foster noble character in students through the process of internalizing Islamic values. The research uses a qualitative case study approach, data collection techniques through interviews, observation, and documentation. The data analysis used is Miles and Huberman’s model: data reduction, data display, and conclusion drawing. The results of the study showed that the strategies used included habituation, role modelling, advice, and discipline. The habituation strategy was carried out through routine religious activities such as joint prayer and congregational prayer. The role model strategy was implemented by providing examples of good behaviour from teachers to students. The advice and discipline strategies were implemented through educational motivation and reprimands. The four strategies complement each other in shaping students' affective aspects, such as attitudes, interests, assessments, and character. The instillation of morals in this context aims for students not only to know the value of goodness cognitively but also to internalize and believe in it in everyday life. Teachers and school administrators need to design and implement strategies that are not only theoretical but also practical in students’ daily lives. Habituation through religious activities and teacher role-modeling can create a conducive learning environment for instilling values.